Effects of Change in Arthritis Severity on Spouse Well-Being: The Moderating Role of Relationship Closeness - Polenick, Courtney A. (J Fam Psychol, 2015)
The severity of a patient’s illness may be detrimental for the psychological well-being of the spouse, especially for those in a particularly close relationship. Using 2 waves of data collected from a sample of 152 knee osteoarthritis (OA) patients and their spouses, we examined associations between change in patients’ illness severity and change in 3 indicators of spouses’ well-being (positive affect, depressive symptoms, and life satisfaction) over a 6-month period. We also tested the hypothesis that spouses’ perceived relationship closeness with the patient would moderate these associations. Consistent with our prediction, a high level of relationship closeness exacerbated the negative impact of increases in patient illness severity on spouses’ positive affect and depressive symptoms over 6 months. Spouses’ life satisfaction declined when patients became more ill, regardless of level of relationship closeness. Our findings highlight the value of examining change in illness as a predictor of change in spouse well-being and the potential downside of relationship closeness for couples living with chronic illness.